Correlations and fault systematics in the Passamaquoddy Bay area, Southwestern New Brunswick - McLeod, M.; Rast, N. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1988)
Three distinct fault-bounded litho-tectonic units have been recognized on Campobello Island in southern Passamaquoddy Bay. These unils are the Upper Silurian Wilsons Beach beds, the Lower Silurian Quoddy Formation and the Upper Precambrian Coldbrook Group. Contact relationships between these units and their correlations in the Passamaquoddy Bay area resolve correlation problems between coastal Maine and New Brunswick, and demonstrate the nature of the junction between the Avalon Platform and the Acadian mobile belt. The Wilsons Beach beds are a remnant of the Acadian belt on northeastern Campobello Island, whereas the Coldbrook Group and the Quoddy Formation represent a fault block of the Avalon Platform. The Coldbrook Group, probably overlain unconformably by the Quoddy Formation, plunges to the southwest beneadi the Quoddy Formation of southeastern Maine. The Siluro-Devonian basins formed in a tensional tectonic regime in response to normal(?) faulting. These faults formed along pre-existing zones of crustal weakness that were generated during the late Precambrian by major strike-slip faulting. The present geological configuration of the area was basically established by episodic reactivation of northeast-trending faults (high-angle reverse movements) during the compressional regime of the Acadian Orogeny,